The Optimal Portofolio Creation using Markowitz Model - Muis, Muhammad Abdul; Adhitama, Satria (AFRE (Accounting and Financial Review), 2021)
The research intends at analyzing the optimal portfolio creation using the Markowitz model (Mean variance) in the Chevron Pacific Indonesia pension fund.The research methodology used is qualitative descriptive method with panel and secondary data obtained from the Chevron Pacific Indonesia pension fund. The sampling technical method used the monthly data during the period January 2016 to December 2018. The data analysis technique used is a portfolio analysis using Markowitz model.In the analysis it was found that during the period. The writer considers investment activities Chevron Pacific Indonesia pension fund hasn't formed efficient portfolio and optimal, only produces an average realization return of 7.93% with a risk 3.50%. While efficient portfolio alternatives by using the mean variance model are: in GMV portfolio produces an expected return 7.93% with a risk 1.45%, while in Tangency portfolio an expected return is 8.07% with a risk 3.73%, while the maximum portfolio return produces an expected return of 10.24% with the highest level risk of 12.24%.Penelitian ini bertujuan untuk menganalisis penciptaan portofolio optimal dengan menggunakan model Markowitz (Mean variance) pada dana pensiun Chevron Pacific Indonesia. Metodologi penelitian yang digunakan adalah metode deskriptif kualitatif dengan panel dan data sekunder yang diperoleh dari dana pensiun Chevron Pacific Indonesia. Teknik pengambilan sampel menggunakan data bulanan selama periode Januari 2016 sampai dengan Desember 2018. Teknik analisis data yang digunakan adalah analisis portofolio dengan menggunakan model Markowitz. Dalam analisis ditemukan bahwa selama periode tersebut. Penulis menilai kegiatan investasi dana pensiun Chevron Pacific Indonesia belum membentuk prtfolio yang efisien dan optimal, hanya menghasilkan realisasi retun rata-rata sebesar 7,93% dengan risiko 3,50%. Sedangkan alternatif portofolio yang efisien dengan menggunakan mean variance model adalah: pada portofolio GMV menghasilkan expected return 7,93% dengan risiko 1,45%, sedangkan pada Tangency portfolio return yang diharapkan adalah 8,07% dengan risiko 3,73%, sedangkan return portofolio maksimum menghasilkan pengembalian yang diharapkan sebesar 10,24% dengan tingkat risiko tertinggi sebesar 12,24%.Â